Extending the Marijuana Gateway Hypothesis Beyond Drug Use to Violent Offending: Examining Dual Systems Imbalance as a Mediator - Wojciechowski, Thomas W. (Crime & delinquency, 2024)
Prior research has posited that marijuana may act as a gateway drug that increases risk for progression to other forms of drug use. However, many cognitive mechanisms posited to underpin this relationship are general risk factors associated with other behaviors also, like violence. This study investigated whether marijuana use initiation during adolescence acts as a gateway to violent offending operating through imbalance in dual systems model construct development. The Pathways to Desistance data were analyzed. Generalized structural equation modeling was used to test for direct and indirect effects of interest. Results indicated that lifetime marijuana use prior to baseline predicted increased wave three violent offending risk. This relationship was significantly mediated by dual systems imbalance as predicted. Implications are discussed.